p140Cap Controls Female Fertility in Mice Acting via Glutamatergic Afference on Hypothalamic Gonadotropin-Releasing Hormone Neurons - Camera, Mattia; Russo, Isabella; Zamboni, Valentina; Ammoni, Alessandra; Rando, Simona; Morellato, Alessandro; Cimino, Irene; Angelini, Costanza; Giacobini, Paolo; Oleari, Roberto; Amoruso, Federica; Cariboni, Anna; et al. (Frontiers in Neuroscience, 2022)
p140Cap, encoded by the gene SRCIN1 (SRC kinase signaling inhibitor 1), is an adaptor/scaffold protein highly expressed in the mouse brain, participating in several pre- and post-synaptic mechanisms. p140Cap KO female mice show severe hypofertility, delayed puberty onset, altered estrus cycle, reduced ovulation, and defective production of luteinizing hormone and estradiol during proestrus. We investigated the role of p140Cap in the development and maturation of the hypothalamic gonadotropic system. During embryonic development, migration of Gonadotropin-Releasing Hormone (GnRH) neurons from the nasal placode to the forebrain in p140Cap KO mice appeared normal, and young p140Cap KO animals showed a normal number of GnRH-immunoreactive (-ir) neurons. In contrast, adult p140Cap KO mice showed a significant loss of GnRH-ir neurons and a decreased density of GnRH-ir projections in the median eminence (ME), accompanied by reduced levels of GnRH and LH mRNAs in the hypothalamus and pituitary gland, respectively. We examined the number of kisspeptin (KP) neurons in the rostral periventricular region of the third ventricle, the number of KP-ir fibers in the arcuate nucleus, and the number of KP-ir punctae on GnRH neurons but we found no significant changes. Consistently, the responsiveness to exogenous KP in vivo was unchanged, excluding a cell-autonomous defect on the GnRH neurons at the level of KP receptor or its signal transduction. Since glutamatergic signaling in the hypothalamus is critical for both puberty onset and modulation of GnRH secretion, we examined the density of glutamatergic synapses in p140Cap KO mice, and we observed a significant reduction in the density of VGLUT-ir punctae both globally in the preoptic area and on GnRH neurons. Our data suggest that the glutamatergic circuitry in the hypothalamus is altered in the absence of p140Cap, and is required for female fertility, independently from the KP system.